An investigation of shedding and super‐shedding of Shiga toxigenic Escherichia coli O157 and E. coli O26 in cattle presented for slaughter in the Republic of Ireland. (22nd October 2018) - McCabe, Evonne; Burgess, Catherine M.; Lawal, Dolapo; Whyte, Paul; Duffy, Geraldine
Summary: Shiga toxigenic Escherichia coli (STEC) are an important group of pathogens and can be transmitted to humans from direct or indirect contact with cattle faeces. This study investigated the shedding of E. coli O157 and O26 in cattle at the time of slaughter and factors associated with super‐shedding (SS) animals. Rectoanal mucosal swab (RAMS) samples were collected from cattle ( n  = 1, 317) at three large Irish commercial beef abattoirs over an 18 month period, and metadata were collected at the time of sampling regarding farm of origin, animal age, breed and gender. RAMS swabs were examined for the presence and numbers of E. coli O157 and O26 using a previously developed quantitative real‐time PCR protocol. Samples positive by PCR were culturally examined and isolates analysed for the presence of stx subtypes, eae and phylogroup. Any samples with counts >10 4  CFU/swab of STEC O157 or O26 were deemed to be super‐shedders. Overall, 4.18% (55/1, 317) of RAMS samples were positive for STEC O157, and 2.13% (28/1, 317) were classified as STEC O157 SS. For STEC O26, 0.76% (10/1, 317) of cattle were positive for STEC O26, and 0.23% (3/1, 317) were classified as super‐shedders. Fewer STEC shedders and SS were noted among older animals (>37 months). There was a seasonal trend observed for STEC O157, with the highest prevalence of shedding and SS events in the autumn (August to October). The majority of E. coli O157 (50/55) isolates had stx2 and were eae positive, with no significant difference between SS and low shedders (LS). Interestingly, all STEC O26 ( n  = 10) were eae negative and had varied stx profiles. This study demonstrates that, while the overall shedding rates are relatively low in cattle at slaughter, among positive animals there is a high level of SS, which may pose a higher risk of cross‐contamination during slaughter.